Developing digital signal clustering method using local binary pattern histogram - Rasras, Rashad J.; Zahran, Bilal; Abu Sara, Mutaz Rasmi; AlQadi, Ziad (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this paper we presented a new approach to manipulate a digital signal in order to create a features array, which can be used as a signature to retrieve the signal. Each digital signal is associated with the local binary pattern (LBP) histogram; this histogram will be calculated based on LBP operator, then k-means clustering was used to generate the required features for each digital signal. The proposed method was implemented, tested and the obtained experimental results were analyzed. The results showed the flexibility and accuracy of the proposed method. Althoug different parameters of the digital signal were changed during implementation, the results obtained showed the robustness of the proposed method.